Transtorno de estresse pós-traumático, variabilidade da frequência cardíaca e dissociação : fundamentos teóricos e influência das variáveis - Oliveira, Fernando Rainho de (2020)
Advances in technology and computer science made the measuring of autonomic balance a reality. As a reliable, noninvasive and inexpensive measure, heart rate variability (HRV) is becoming largely studied in human cognition. Its low rates are associated with greater symptoms severity and mental disorders. The studies regarding HRV, as well as other psychophysiological markers, will help in a better understanding of mental disorders such as posttraumatic stress disorder (PTSD). PTSD is understood as a group of manifest symptoms (i.e. intrusions, avoidance, changes in cognition and mood, changes in arousal and psychophysiological reactivity) present after the individual experiences a traumatic situation. Another manifestation form of PTSD, named Dissociative subtype, is possible, which is when dissociation symptoms are also present. Currently, few studies between HRV and PTSD control the presence of dissociation symptoms, which can be acting as a confounding variable. An issue that may be contributing to the lack of understanding, and therefore control of the dissociation, is the very definition of the term, criticized for being too generalist. This dissertation includes a theoretical introduction and an empirical study that seek to help fill the gap in studies between PTSD, HRV and dissociation. First, the theoretical introduction provides a brief presentation on the concepts of PTSD and HRV, as well as a historical view of how dissociation was perceived and defined over time. Following the theoretical introduction, an empirical study is presented. The article proposes an analysis of the influence of HRV on PTSD symptoms, taking into account dissociation symptoms. Once dissociation variable being controlled, results went in a contrary direction to what has been previously described in literature. This fact leads us to highlight the importance of correctly measuring the presence of dissociation in researches. Based on our findings, suggestions for future studies are proposed.